(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The aim of this work is the exhibition of the influence of the institution of public sector, in this case the Command of Municipal Police, on creating the safety conditions in Koszalin.The efficient functioning of institutions responsible for safety is the impor-tant element of public life. The paper aims at showing how expenses are connected with realizing tasks by institutions assuring safety in Koszalin. The author also wanted to expose the influence of the Police and its workings on safety of the occupants of the town. Essential role is also played by principles of working of this institution, ways of spendings money on realization of tasks as well as the effectiveness of executed work-ings.